2020
DOI: 10.1002/jso.25878
|View full text |Cite
|
Sign up to set email alerts
|

Malignant fibrous histiocytoma of bone: A survival analysis from the National Cancer Database

Abstract: Background and Objectives: Malignant fibrous histiocytoma (MFH) of bone, now known as undifferentiated pleomorphic sarcoma of bone, is a rare neoplasm that accounts for less than 2% of all primary malignant bone tumors. The objective of the current study was to evaluate prognosis and survival for MFH of bone. Methods: The 2004 to 2016 National Cancer Database was queried to identify patients with a primary MFH of bone. Kaplan-Meier survival and Cox regression analyses were used to analyze overall survival and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Related reports suggest that the recurrence rate of UPS is greater than 31% ( 13 ). Compared with other STSs, the 5-year overall survival (OS) rate is lower in UPS, around 50–70% ( 9 , 14 - 16 ), and some studies revealed that the 5-year OS rate could be 72% ( 17 ). Surgical treatment is largely followed in the UPS ( 16 , 18 ), which can achieve significantly local control for primary UPS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Related reports suggest that the recurrence rate of UPS is greater than 31% ( 13 ). Compared with other STSs, the 5-year overall survival (OS) rate is lower in UPS, around 50–70% ( 9 , 14 - 16 ), and some studies revealed that the 5-year OS rate could be 72% ( 17 ). Surgical treatment is largely followed in the UPS ( 16 , 18 ), which can achieve significantly local control for primary UPS.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other STSs, the 5-year overall survival (OS) rate is lower in UPS, around 50–70% ( 9 , 14 - 16 ), and some studies revealed that the 5-year OS rate could be 72% ( 17 ). Surgical treatment is largely followed in the UPS ( 16 , 18 ), which can achieve significantly local control for primary UPS. Forty percent of patients with these tumors develop pulmonary metastases ( 15 ), which was with 8–12 months of median survival ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that advanced age is an independent risk factor for poor prognosis [26,27]. Lou et al [3]revealed that an age ≥ 55 years were independently associated with poor overall survival in spinal UPS.…”
Section: Discussionmentioning
confidence: 99%
“…Related reports suggest that the recurrence rate of UPS is greater than 31% [12]. Compared with other STSs, the 5-year survival rate is lower in UPS, around 50-70% [9,[13][14][15], and some studies revealed that the 5-years OS rate could reach 72% [16]. Surgical treatment is largely followed in the UPS [15,17], which can achieve signi cantly local control for primary UPS.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other STSs, the 5-year survival rate is lower in UPS, around 50-70% [9,[13][14][15], and some studies revealed that the 5-years OS rate could reach 72% [16]. Surgical treatment is largely followed in the UPS [15,17], which can achieve signi cantly local control for primary UPS. 40% of patients with these tumors develop pulmonary metastases [14], which was with 8-12 months of median survival [18].…”
Section: Introductionmentioning
confidence: 99%